Valuation of enviromental resources - The case of orangutans in nature reserves in Sarawak - Christina Annette, Jinam (2011)
The orangutan is an iconic and endangered species of ape found only in Borneo and Sumatra. In Sarawak, orangutans that are undergoing rehabilitation are kept in national parks and nature reserves such as Semenggoh Wildlife Centre and Matang Wildlife Centre. These parks are open to the public and they also contain other attractions apart from the orangutan, such as plants, other wildlife and activities such as trekking. This study aims to find out the economic value of the orangutans and the other park attractions to the visitors) This is done by trying to elicit their willingness to pay (WTP) to see the orangutans and other park attractions using the contingent valuation method, that is, by directly asking them for their WTP using questionnaires. The study found that visitors do indeed give a higher value to the orangutan and the parks than the existing entrance fee, and this value can be used by park authorities in decision making regarding the use of these natural resources.